Patient democracies? - Sára Khayouti; Hubert János Kiss; Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We test if the political regime of a country associates with the patience of the citizens. Recent findings indicate that i) more democratic countries tend to have higher growth, and ii) patience correlates positively with economic development, suggesting a potential link between the political regime and patience. We document a positive association between the level of democracy and patience for most of the political regime indices that we use, even after controlling for region, economic development, geographical conditions, and culture. We report some evidence that political participation is behind our findings.
Keywords: D02; D12; 330; democracy; patience; political regime; time preferences